Characterization of mulberry leaf instant tea and evaluation of its hypolipidemia effect via regulation of intestinal microbiota - Xiaoyun Han; Yunlong Bai; Xiaoxin Feng; Baochang Du; Baojiang Zheng; Qingshen Sun (Food Science and Human Wellness)
The purpose of this study was to characterize mulberry leaf instant tea (MLIT) powder prepared from the‘Longsang No. 1’ (Morus abla L. cv. Longsang 1) mulberry leaves in Heilongjiang Province (China) and assess its obesity-preventing/relieving effects. A total of 174 compounds including quercetin, chlorogenic acid, 1-deoxyecomycin (1-DNJ) related to antihyperlipidemia effects were identif ied from the MLIT powder.MLIT treatment reversed the Lee’s index, fat coefficient, and serum biochemical parameters in both the obesity relieving and obesity preventing mice fed with high-fat diet. In the obesity relieving experiment, the relative abundance of Desulfovibrio in mouse feces decreased after both 0.5% and 1% MLIT treatments. In obesity preventing experiments, mouse with different amount of MLIT treatments showed increased relative abundance of Akkermansia, Bifidobacterium and Lactobacillus, while Deferribacteres, Desulfobacterota decreased. The beneficial bacteria in the intestinal tract of mice treated with MLIT increased. This study proved that MLIT had antihyperlipidemia potential via modulating intestinal microbiota in mice.